1999
DOI: 10.1098/rstb.1999.0490
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of human autosomes

Abstract: Comparative gene mapping and chromosome painting permit the tentative reconstruction of ancestral karyotypes. The modern human karyotype is proposed to differ from that of the most recent common ancestor of catarrhine primates by two major rearrangements. The first was the fission of an ancestral chromosome to produce the homologues of human chromosomes 14 and 15. This fission occurred before the divergence of gibbons from humans and other apes. The second was the fusion of two ancestral chromosomes to form hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
31

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 152 publications
1
36
0
31
Order By: Relevance
“…Interestingly, the conservative nature of chromosomal evolution detected in the low-numbered afrotherians extends also to man. In addition to the X chromosome, we and others (Haig 1999;Murphy et al 2003;Richard et al 2003b;Yang et al 2003) have shown that 14 out of the 22 human autosomes (HSA 1,3,(4)(5)(6)9,11,(13)(14)(15)(17)(18)(20)(21) have been retained in toto in representatives of the four major eutherian clades. This reflects their probable occurrence in the last common ancestor of all Placentalia and emphasizes the long conserved evolutionary history of these chromosomes, and by extension that of the human genome.…”
Section: (B) Genome Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the conservative nature of chromosomal evolution detected in the low-numbered afrotherians extends also to man. In addition to the X chromosome, we and others (Haig 1999;Murphy et al 2003;Richard et al 2003b;Yang et al 2003) have shown that 14 out of the 22 human autosomes (HSA 1,3,(4)(5)(6)9,11,(13)(14)(15)(17)(18)(20)(21) have been retained in toto in representatives of the four major eutherian clades. This reflects their probable occurrence in the last common ancestor of all Placentalia and emphasizes the long conserved evolutionary history of these chromosomes, and by extension that of the human genome.…”
Section: (B) Genome Conservationmentioning
confidence: 99%
“…The paenungulates all have high chromosome numbers (Sirenia 2n = 48-56, Proboscidea 2n = 56, Hyracoidea 2n = 54), while the Afroinsectiphillia have low numbers (Tubulidentata 2n = 20, Macroscelidea 2n = 26-34, Afroinsectivora 2n = 28-36 in golden moles). Because the size and number of the conserved adjacent homologous segments reflect the number of rearrangements that have occurred in evolution, and the difference in chromosome numbers of the species that are compared, we anticipated that the low-numbered afrotherians would provide additional information on the eutherian ancestral karyotype (Chowdhary et al 1998;Haig 1999;Wienberg et al 2000;Murphy et al 2001c;Richard et al 2003b;Yang et al 2003). Second, given the uncertainty regarding many of the evolutionary relationships within the Afrotheria, we set out to determine whether we could identify shared derived chromosomal states that would provide evidence, independent of sequence data, of the phylogenetic associations among aardvark, golden moles and the elephant-shrews (Afroinsectiphillia).…”
Section: Introductionmentioning
confidence: 99%
“…d Evidence has indicated that the two arms of these chromosomes were unlinked in a primate ancestor (Haig 1999;Richard et al 2000Richard et al , 2003Murphy et al 2001;Carbone et al 2002;Misceo et al 2003).…”
Section: Bes Mate Pairs For Mammalian Genome Comparisonmentioning
confidence: 99%
“…12. Chromosome rearrangement is a key event in speciation; new species almost always have a new karyotype [84][85][86]. On possible role of the satDNAs and HRs chromosomes in the evolution of plants and animals there is a vast amount of publications (see [5][6][7][8]).…”
Section: Why Ncdnas?mentioning
confidence: 99%